Synthesis of Fused Oxepane HIV Integrase Inhibitor MK-1376 - Maligres, Peter E.; Song, Zhiguo Jake; Strotman, Neil A.; Yin, Jinquin; Pei, Tao; Strotman, Hallena R.; Itoh, Tetsuji; Sherer, Edward C.; Humphrey, Guy R. (Synthesis, 2020)
Controlling the absolute and relative stereochemistry of a seven-membered oxepane in the formation of HIV integrase inhibitor MK-1376 was accomplished through a strategy involving the use of asymmetric allylation and stereoconvergent, substrate-directed installation of an amine fragment. Surprising reactivity was demonstrated during the asymmetric allylation in which the allyl-pyrimidone product was formed reversibly. The stereoconvergent amine addition was accomplished through an elimination/addition sequence involving a quinone methide reactive intermediate, and nucleophilic trapping of the reactive quinone methide intermediate with methylamine. This novel approach delivered MK-1376, offering 100-fold greater productivity and 50-fold less waste than the initial synthetic chemistry route.
Keywords: HIV integrase inhibitor; oxepane; pyrimidine; π-allyl cyclization; quinone methide